Financial education, financial management in users of banking entities in the province of San Martín - Gabriel Pérez, Talita (2021)
The main objective of this research work was to determine the significant relationship between financial education and financial management of users of banking entities in the province of San Martín. The scope of the study was quantitative, non-experimental cross-sectional design of correlational scope, non-probabilistic sampling for convenience consisted of 290 users, whose ages ranged from 18 to 56 years (44.48% men and 55.52% women); to whom the financial education and financial management questionnaire was administered. The results found indicated that there is a significant correlation between financial education and financial management (r = .779; p < .001). Likewise, a highly significant positive relationship was found between financial education and financial management dimensions: income planning (rho = .606; p <.001), credit situation (rho = .484; p < .001), budgets (rho = .732; p < .001) and saving habits (rho = .506; p < .001). Similarly, a positive relationship was found between financial management and financial education dimensions: financial knowledge (rho = .623; p < .001), financial ability (rho = .638; p < .001), financial attitude (rho = .551; p < .001) and financial awareness (rho = .693; p < .001). It is concluded that the greater the financial education the users will have greater skills to manage their finances and vice versa.